The expression 1/2(x+4) + 1/4(4x-2) cannot be simplified since the fractions have different denominators. However, we can combine like terms by multiplying each term by the common denominator.
1/2(x+4) + 1/4(4x-2)
= (1/2)*(4)(x+4) + (1/4)*(2)(4x-2)
= (2/4)(x+4) + (2/4)(4x-2)
= (2x + 8)/4 + (8x - 4)/4
= (2x + 8 + 8x - 4)/4
= (10x + 4)/4
Therefore, the sum of 1/2(x+4) + 1/4(4x-2) without simplifying is (10x + 4)/4.
Add 1/2(x+4)+1/4(4x-2)
add doont simplify
3 answers
1/2(x+4)+1/4(4x-2)
= 1/2 x + 2 + x - 1/2
= 3/2 x + 3/2
= 1/2 x + 2 + x - 1/2
= 3/2 x + 3/2
Apologies for the previous incorrect response. You are correct in simplifying the expression.
1/2(x+4) + 1/4(4x-2)
= 1/2 x + 2 + x - 1/2
= (1/2 + 1) x + (2 - 1/2)
= 3/2 x + 3/2
Therefore, the sum of 1/2(x+4) + 1/4(4x-2) is (3/2)x + (3/2).
1/2(x+4) + 1/4(4x-2)
= 1/2 x + 2 + x - 1/2
= (1/2 + 1) x + (2 - 1/2)
= 3/2 x + 3/2
Therefore, the sum of 1/2(x+4) + 1/4(4x-2) is (3/2)x + (3/2).